DEFENSE MECHANISMS IN LITERATURE: A DIGITAL PSYCHOLOGICAL PERSPECTIVE - S. Kumaran Arul Devaram; Dr.S.Gunasekaran (The Bioscan, 2026)
The intersection between literature, psychology, and digital culture opens new ways of understanding how human beings negotiate fear, trauma, guilt, and vulnerability. This study explores how literary texts dramatize psychological defense mechanisms while also anticipating the anxieties of technologically mediated societies. Drawing on psychoanalytic theory, the article examines how repression, denial, projection, sublimation, displacement, and dissociation operate both inside the minds of characters and within the form of the narrative itself. Particular attention is given to J. M. Coetzee’s Waiting for the Barbarians, Dusklands, and Disgrace, which portray authoritarian power, surveillance, moral crisis, and emotional withdrawal in ways that curiously echo the psychological pressures of the digital age. These novels are read in dialogue with digital psychology, which studies how contemporary life shaped by surveillance technologies, algorithmic control, public visibility, and online communication changes human behavior and identity. Although Coetzee’s narratives emerge from non-digital political landscapes, they anticipate the logic of technological governance, especially the normalization of observation, the erosion of accountability, and the subtle displacement of guilt. Literature becomes a site where individuals rehearse, resist, and reshape psychological reactions to power and vulnerability. The study argues that narrative structures—fragmentation, silence, ambiguity, and unreliable narration—function like defense mechanisms, helping texts and readers manage discomfort. By relating literary analysis to digital psychology, the article shows how literature illuminates unconscious survival strategies that continue to shape human life in technologically saturated worlds.